The Influences of the Tax System, Tax Rate, Tax Audit and Tax Discrimination on Tax Evasion by Body Taxpayer - Allita Prisantama; Muqodim Muqodim (The Indonesian Journal of Accounting Research, 2016)
Abstract: The objective of this research is to analyze the influence of the tax system, tax rate, tax audit and tax discrimination on tax evasion. This survey research is using the questionnaire as an instrument. The population in this research are all body taxpayers in the form of Incorporate Company or Commmanditaire Vennootschaap located in Yogyakarta Province. The research samples are selected using a random sampling method. Total of samples is 42 body taxpayers in Yogyakarta Province in the form of Incorporate Company and Commmanditaire Vennootschaap. The data is analyzed using multiple regression analysis with SPSS (Statistical Product and Service Solution) version 23. The result of hypothesis testing conclude that: (1) tax system variable has positive and significant effect toward tax evasion, (2) tax rate has negative and insignificant effect toward tax evasion, (3) tax audit has negative and insignificant effect to tax evasion and (4) tax discrimination has positive and significant effect to tax evasion. Abstrak: Tujuan dari penelitian ini adalah untuk menganalisis pengaruh sistem perpajakan, tarif pajak, pemeriksaan pajak, dan diskriminasi pajak terhadap penggelapan pajak. Penelitian ini menggunakan kuesioner sebagai instrumen. Populasi dalam penelitian ini adalah seluruh wajib pajak badan dalam bentuk Perseroan Terbatas (PT) atau Commmanditaire Vennootschaap (CV) yang berada di Provinsi Yogyakarta. Sampel penelitian dipilih dengan menggunakan metode random sampling. Total sampel dalam penelitian ini adalah sebanyak 42 wajib pajak badan di Provinsi Yogyakarta dalam bentuk Perseroan Terbatas (PT) dan Commmanditaire Vennootschaap (CV). Data dianalisis menggunakan analisis regresi berganda dengan software SPSS (Statistical Product and Service Solution) versi 23. Dari hasil pengujian hipotesis dapat disimpulkan bahwa: (1) variabel sistem perpajakan berpengaruh positif dan signifikan terhadap penggelapan pajak, (2) variabel tarif pajak berpengaruh negatif dan tidak signifikan terhadap penggelapan pajak, (3) variabel pemeriksaan pajak berpengaruh negatif dan tidak signifikan terhadap penggelapan pajak, dan (4) variabel diskriminasi pajak berpengaruh positif dan signifikan terhadap penggelapan pajak.